2010
DOI: 10.1520/jai102334
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Temperature and Heat Flux in Furnaces Controlled by Different Types of Temperature Sensors

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…The heat flux for the F2 furnace curve would have continued to increase until approximately 60 minutes when the decay phase of the programed furnace curve began. Based on previous work, the heat flux during the standard fire curve would have continued to roughly 175 kW/m 2 at 2 hours . While the peak heat flux occurred faster in the design fire furnace curves (F1 and F2) when compared with the standard fire curve, the maximum heat fluxes are still below what would be expected in an actual fire compartment.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The heat flux for the F2 furnace curve would have continued to increase until approximately 60 minutes when the decay phase of the programed furnace curve began. Based on previous work, the heat flux during the standard fire curve would have continued to roughly 175 kW/m 2 at 2 hours . While the peak heat flux occurred faster in the design fire furnace curves (F1 and F2) when compared with the standard fire curve, the maximum heat fluxes are still below what would be expected in an actual fire compartment.…”
Section: Discussionmentioning
confidence: 90%
“…Sultan, et al found that the furnace temperature measuring device response time is crucial in assessing building elements performance particularly in a short duration tests . The furnace temperatures here were controlled based on measurements made by thermocouples inside protection pipes as specified in ASTM E119 .…”
Section: Discussionmentioning
confidence: 99%
“…The plate thermometer measures the effective temperature of the specimen inside a refractory furnace during a fire-resistance test [42]. Additionally, the plate thermometer can also be used for measuring heat flux in several fire experiments [43][44][45][46]. The construction of the plate thermometer is given in EN1363-1 and ISO 834-1.…”
Section: Fire-resistance Furnacesmentioning
confidence: 99%
“…What is more, the average temperature of the furnace during the test is measured by several Type K chromel-alumel thermocouples which are placed in specimen (Mostafaei, 2013). However, it has been stated that there exists a significant difference between furnace temperatures measured by different types of thermocouples, expecially at the begning of the operation (Sultan, 2010). Besides, due to the high costs of furnaces, many specimens were tested in a single furnace at the same time (Anagnostopoulos, Sideris, & Georgiadis, 2009).…”
Section: Conventional Fire Tests Of Concretementioning
confidence: 99%